The view and policy of management of occupational health services on the performance of workers' health surveillance: a qualitative exploration - Felicia S. Los; Carel T. J. Hulshof; Judith K. Sluiter (BMC, 2019)
Abstract Background Although workers' health surveillance is an important preventive activity, it is not regularly performed. In addition to the occupational physician, the management of occupational health services can also be involved in the performance of workers' health surveillance. The present study investigated the view and policy of the managements of occupational health services on the performance of workers' health surveillance by occupational physicians. Method Semi-structured face-to-face interviews about the mission, view, and policy of the occupational health services with respect to workers' health surveillance were conducted with eighteen randomly selected board members of occupational health services in the Netherlands. The results were transcribed verbatim and were analysed using MAXQDA software to form themes and categories. Results The first theme found was the view of the management of occupational health services. Categories found were mission statements of occupational health services and the attitude of the management of occupational health services towards workers' health surveillance. Three types of mission statements were mentioned by the board members: keeping workers at work, improving the health of workers, or helping the employer with sick-leave management. Both positive and negative attitudes towards workers' health surveillance appeared from the interviews. Some board members mentioned that workers' health surveillance can improve workers' health, and creates awareness about workers' health. Other board members mentioned that performing workers' health surveillance is eliciting problems, and that employers do not have a positive attitude towards workers' health surveillance. The second theme was the policy on performing workers' health surveillance. Categories found were the policy on performing workers' health surveillance towards companies, and the policy on performing workers' health surveillance towards professionals. Some occupational health services recommend workers' health surveillance to all companies. However, in general workers' health surveillance was only performed at request of companies, and no instructions or training programmes for occupational physicians were provided. Conclusion Although some of the mentioned views on workers' health surveillance are positive, the policy of occupational health services on workers' health surveillance does, so far, in general, not stimulate occupational physicians or employers to perform or organize workers' health surveillance.